The effect of cigarette smoking on human seminal parameters, sperm chromatin structure and condensation. (9th November 2017) - Mostafa, R. M.; Nasrallah, Y. S.; Hassan, M. M.; Farrag, A. F.; Majzoub, A.; Agarwal, A.
Summary: Considerable debate still exists regarding the effects of cigarette smoking on male fertility. This work aimed to explore effects of cigarette smoking on semen parameters and DNA fragmentation on 95 infertile patients who were divided into infertile male nonsmokers (45) and infertile male smokers (50). Smokers were subdivided according to a number of cigarettes smoked per day into mild (≤10), moderate (11‐20) and heavy smokers (≥21). Semen analysis, sperm chromatin condensation integrity with aniline blue staining and sperm viability were compared between the study groups. A significant decrease has been shown in sperm count ( p  = .006), progressive motility ( p  = <.001), percentage of normal forms ( p  = <.001) and viability ( p  = .002) between infertile nonsmoker and infertile smokers. The percentage of abnormal sperm chromatin condensation was significantly higher in smokers compared to nonsmokers ( p  = <.001). A linear correlation was detected between the extent of cigarette smoking and the degree of worsening in progressive motility ( p  = .001), total motility ( p  < .001), viability ( p  < .001) and normal morphology ( p  < .001). These results indicate that cigarette smoking has detrimental effects on semen parameters. It negatively affected all conventional semen parameters in addition to sperm chromatin condensation and sperm viability. These abnormalities were also proportional to the number of cigarettes smoked per day and to the duration of smoking.